Changes in biochemical properties of tomato (cv.240) affected by combination of blue/red optical spectra and Calfomyth spray (Ca and P) - Ajdanian, Ladan; Aroiee, Hossein; Azizi, Majid; Babaei, Mehdi (International Journal of Agricultural and Biological Engineering, 2020)
The levels of antioxidant activity and vitamins can change with varying ratios of different wavelengths. This study was conducted as a pot experiment under soilless culture conditions in order to investigate the interactive effects of light supplementation and nutrition (calfomyth solution) on some qualitative traits of tomato fruit. The research was carried out as a split-plot experiment based on a completely randomized design with three light treatments including without supplementary light (control), 60% red light+40% blue light and 90% red light+10% blue light. There were two nutritional treatments including no spraying with calfomyth as commercial fertilizer and foliar application with a concentration of 2 mg/L in three replicates. According to the results, the amounts of vitamin C (16.1 mg/g FW fruit), soluble solids (12.33 mg/g FW fruit), and lycopene (2.95 mg/g FW fruit) were all uppermost by the effect of a higher percentage of red light treatment. Higher percentage of the blue light resulted in the highest leaf chlorophyll content (38.4 mg/g FW leaf), but supplementary light treatments had no significant effects on the titratable acidity. Nutrition (calfomyth foliar application) showed positive impacts on all treatment traits compared to control. Beta-carotene content was affected by none of the treatments with no significant differences. According to this research, it can be expected that the use of complementary light treatments and calfomyth foliar spray may have positive effects on most of the qualitative traits in tomato fruit (cv. 240). Keywords: biochemical properties, tomato, optical spectra, calfomyth, antioxidant, lycopene, phytochrome DOI: 10.25165/j.ijabe.20201305.5797 Citation: Ajdanian L, Aroiee H, Azizi M, Babaei M. Changes in biochemical properties of tomato (cv.240) affected by combination of blue/red optical spectra and Calfomyth spray (Ca and P). Int J Agric & Biol Eng, 2020; 13(5): 79–84.